Memilih Tidak Berubah Sebagai Strategi Pemasaran Ditengah Revolusi Industri Yang Cepat Berubah Demi Keberlangsungan Hidup Dan Citra Destinasi Wisata (Studi Kasus pada Usaha Kecil dan Kafe Sawah Desa Wisata Pujon Kidul Kabupaten Malang) - Hari Purwanto; Dian Citaningtyas Ari Kardi (Tirtayasa Ekonomika, 2021)
The tourist destination of Café Sawah in Pujon Kidul village, Malang district is one of the self-made tourist destinations that are considered successful and provide great benefits for improving the economy of the residents of Pujon Kidul village. The success of the Sawah Café tourist destination cannot be separated from the use of natural strategic locations and the role of the media. social media which is very helpful in promoting this place as a viral destination and is immediately widely recognized. The purpose of this case study is to examine the potential and obstacles to the survival of small businesses and tourist destinations, Café Sawah Pujon Kidul, Malang Regency. This approach is qualitative with case studies. The informants of this research include tourism village managers, tourist visitors, small traders in tourist villages, the surrounding community. Data analysis includes (1) data collection (2) data display (3) data reduction and (4) conclusions. (Miles, Mathew B., 1994) The results show the dependence of tourist visits and the sustainability of small businesses in the village of Pujon Kidul with the potential of natural locations which are the main competitive advantages. Another factor of finding a competitive advantage, conservation of the natural environment, and rejection of investment from outside Pujon Kidul are the keys to realizing sustainable management of tourism villages and not developing into uncontrolled tourist destinations.